Changes in self-rated health and subjective social status over time in a cohort of healthcare personnel. (September 2014) - Thompson, Mark G; Gaglani, Manjusha J; Naleway, Allison; Thaker, Swathi; Ball, Sarah
As part of a prospective cohort study of 1354 female and 347 male healthcare personnel, we examined the stability of subjective social status over 7 months and the prospective association between subjective social status and self-rated health status. Most (82%) subjective social status ratings were stable (within ±1 point). Lower baseline subjective social status among healthcare personnel was associated with more subsequent reports of fatigue and headache and worsening global self-rated health status. Healthcare personnel who placed themselves on the bottom half of the subjective social status ladder were four times more likely to experience a decline in global self-rated health status and half as likely to improve to excellent self-rated health status.